Evaluation study of the IFPRI/A4NH research program on diet quality and health of the poor - Behrman, Jere R.; Ghosh, Shibani (International Food Policy Research Institute, 2019)
IFPRI’s Poverty, Health, and Nutrition Division (PHND) and the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) have conducted research on the critical links between nutrition, health, and agriculture since 2003. The work began at IFPRI as Global Research Program 24 (GRP24) on Diet Quality and Health of the Poor and evolved over time, becoming part of IFPRI’s Strategic Research Area 2: Promoting Healthy Food Systems (Programs and Policies to Improve Nutrition) and then, in 2012, it became the flagship on Integrated Programs and Policies for Nutrition within A4NH. This evaluation, which was commissioned jointly by IFPRI and A4NH, covers the impact of the combined research program from 2003 to the end of the first phase of the A4NH flagship program in 2016. During this timeframe, the work of the research program was carried out through some 140 projects, among which some of the most important were Alive & Thrive (A&T), Partners and Opportunities for Strengthening and Harmonizing Actions for Nutrition in India (POSHAN), Transform Nutrition (TN), Stories of Change (SoC), Leveraging Agriculture for Nutrition in South Asia (LANSA), and Advancing Research on Nutrition and Agriculture (ARENA), with funding from a number of donors. Key questions posed for the evaluation include: Did IFPRI/A4NH have the right research strategy and make appropriate adaptations based on internal learning, stakeholder and partner inputs, and evolving circumstances? Has IFPRI/A4NH been effective in identifying, engaging, and supporting key partners and influencing its target audiences: other researchers, development program implementers, policymakers, and donors? How effective has IFPRI/A4NH been in increasing partner capacity, especially in developing countries, for identifying and analyzing data for better investment and policy decisions and designing, implementing, and evaluating multisectoral agriculture-nutrition health linked interventions? What has been the impact of the programs and policies that IFPRI/A4NH influenced? To support this assessment, we consulted with researchers, clients, and other stakeholders. We selected India and Ethiopia for in-depth case studies in consultation with GRP24 and A4NH staff. These two countries accounted for a large share of the program’s budget. In Ethiopia, PHND/GRP24 invested substantially in evaluation of the Productive Safety Net Program (PSNP) and in India, projects have focused largely on maternal and child nutrition. We conducted 39 interviews with participants, partners, and stakeholders associated with the work conducted in these countries. Interview questions were tailored to the interviewee, but generally addressed experiences with the program, how well the program achieved its objectives, how well it used relevant approaches and methods, and to what extent it contributed to capacity building. Some caveats regarding the information gleaned from the interviews should be mentioned: the interviewees do not constitute a representative sample, and many had worked for GRP24, A4NH, or IFPRI; interviews were conducted in 2018, so answers are likely skewed toward more recent events; and not all interviewees were able to distinguish work under this program from similar or related work. In addition, we reviewed numerous documents, including proposals, project abstracts, internal reviews, and research outputs, as well as measures of impact of the publications produced by the program.